Habitat Suitability Distribution of Genus Gynoxys Cass. (Asteraceae): An Approach to Conservation and Ecological Restoration of the Andean Flora in Peru. - Coronel Castro, Elver (2025)
The study used species distribution models (MaxEnt) to analyze the ecological suitability of the genus Gynoxys in Peru. Bioclimatic, edaphic and topographic variables were integrated to predict areas with high development potential. Potential distribution maps were generated, and model validation showed outstanding performance (AUC > 0.9). The results indicated that variables such as minimum temperature in the warmest season and soil moisture are determinants in the distribution of the Discoide, Gynoxys and Praegynoxys clades. It is concluded that the conservation of the genus requires protection strategies to ensure the sustainability of these montane ecosystems.